Epichloë fungal endophytes play a fundamental role in New Zealand grasslands. Issue 2 (2nd April 2020) - Hume, David E.; Stewart, Alan V.; Simpson, Wayne R.; Johnson, Richard D.
ABSTRACT: Epichloë fungal endophytes that systemically colonise cool-season grasses have become an internationally well-researched symbiosis. While sexual species of Epichloë can cause choke disease of grass seed heads, asexual forms are symptomless endophytes that colonise embryos to become seed transmitted. In mutualistic associations, the grass benefits through greater tolerance of abiotic and biotic stresses. In New Zealand, at least 12 species of naturalised and native grasses have been documented as infected with a range of asexual or sexual Epichloë . The impact of endophyte-infected ryegrass and tall fescue has been significant for pastoral farmers, with Epichloë enhancing pasture performance. Production of bioactive secondary metabolites reduces herbivory by invertebrate pests but some are also toxic to grazing animals. Selected strains of Epichloë have been utilised to reduce livestock problems while retaining improved pasture performance. Documented Epichloë -infected native grasses are rare, justifying greater efforts of discovery, description and conservation as taonga (a treasure) for Māori and all New Zealanders. Given their ecological success in New Zealand ecosystems, along with economic and environmental benefits, there are good prospects to further develop both endemic and naturalised Epichloë -grass associations that may benefit other cool-season grasses and potentially deliver new beneficial properties.